Sector overview and study design - Rashid, Shahidur; Ahmad, Kaikaus; Rosenbach, Gracie (International Food Policy Research Institute, 2019)
The fisheries sector in Bangladesh is important in terms of both economic and food security perspectives. The sector accounts for about 4 percent of national gross domestic product (GDP), 23 percent of the agricultural GDP, and about 3 percent of total foreign exchange earnings (Bangladesh, DoF 2015). In terms of employment, the sector’s role in the economy is even larger. About 17.8 million Bangladeshis, including 1.4 million women, find jobs (full time and part time) in the sector (FAO 2016), which translates to about 11 percent of the total population and more than 23 percent of the working population.1 Fish also occupies an important place in Bangladeshi diets and culture—so much so that there is a Bengali (both Bangladesh and Indian West Bengal) adage that says mache bhate bangali (meaning “fish and rice is what makes a Bengali”). The role of fish in improving food security of the poor is even greater. Fishing is an important source of livelihood for the poor, and it is often their only source of protein. It is estimated that about 70 percent of the rural population engaged in fishing for subsistence at some point in the year (FAO 2014).